Studi Netnografi Produk Viral pada Media Sosial Instagram: Studi Netnografi Produk Viral pada Media Sosial Instagram: Antara Keputusan dan Kepuasan Pelanggan Mixue - Setiawan, Harry; Ginting, Rafles (Eksos, 2024)
This research aims to understand and analyze Mixue's customer decisions and satisfaction on the social media platform Instagram. It also seeks to identify the factors that influence purchase decisions and customer satisfaction regarding Mixue products. Additionally, the research aims to provide recommendations to the company on how to improve customer decisions and satisfaction. The study utilizes a qualitative research method with a netnography approach. Based on the findings of the research, two types of responses from the participants were observed: positive and negative responses. Positive responses indicate satisfaction with the decisions made, while negative responses reflect dissatisfaction with the decisions. There are several triggers for customer satisfaction and dissatisfaction, including price, product quality, and product halal status. One limitation of this research is the relatively small number of participants. For future research, it is recommended to involve more than seven participants to enable comparisons. Additionally, the study was limited by the data collection methods, which relied on passive observation and literature review. Future research could benefit from using in-depth interviews to obtain more profound insights.